Fuel cycle analysis based evaluation of the fuel and emissions reduction potential of adapting the hybrid technology to tricycles - Biona, Jose Bienvenido Manuel M. (Animo Repository, 2007)
A preliminary analysis has been conducted to investigate the fuel use and emissions reduction potential of incorporating hybrid systems to two stroke powered tricycles in Metro Manila. Carbureted and direct injection two stroke engine hybrid systems were investigated and compared with the impact of shifting to four stroke engines. Results showed that hybridized direct injection retrofitted two stroke powered systems would be able to provide far better environmental and fuel reduction benefits than the shift to new four strokes tricycles. It is thus recommended that the development of such technology specifically for tricycles be seriously pursued.